Facebook privacy management strategies: A cluster analysis of user privacy behaviors. (November 2017) - Lankton, Nancy K.; McKnight, D. Harrison; Tripp, John F.
Abstract: Online privacy management research related to e-commerce mainly focuses on whether or not to disclose information. Online social networking on the other hand, offers a broader set of privacy management behaviors such as using vendor-provided privacy settings, limiting self-disclosures, and managing network size. While much prior research has examined these privacy behaviors individually, we investigate how Facebook users combine these behaviors to form privacy management strategies. Using communications privacy management and impression management theories we first develop four propositions about possible user strategies that combine differing levels of disclosure, network size, and privacy setting use. One strategy is the most public, whereas two others deviate from this public strategy by either limiting disclosures, or using privacy settings to restrict access. The final strategy is the most private. We then survey two samples of Facebook users (college students and the general population) about their privacy management behaviors, privacy perceptions, technology usage perceptions, and demographics. Using cluster analysis we find some support for all four propositions, and for an additional strategy that beginning users may employ. The findings also reveal intriguing differences among the privacy management strategies in terms of perceptions and demographics like privacy concern, usefulness, enjoyment, and age, gender, and experience. Implications for future research are discussed. Highlights: Privacy behaviors work together to form four privacy management strategies. The most public strategy discloses more and uses privacy settings less. Two others deviate from this by limiting disclosures or using privacy settings. Another is the most private with less disclosures and more privacy setting use.